2019
DOI: 10.5114/ada.2019.82824
|View full text |Cite
|
Sign up to set email alerts
|

Type D personality, anxiety sensitivity, social anxiety, and disability in patients with acne: a cross-sectional controlled study

Abstract: IntroductionAcne has long been associated with many psychiatric comorbidities.AimTo determine anxiety and depression levels, social phobia frequency, social anxiety level, subjective stress perception, anxiety sensitivity, disability, and the frequency of type D personality in patients with acne.Material and methodsIn total, 61 patients with acne aged > 16 years and 61 age, gender, and educationally matched healthy volunteers were included in the study. The patients and healthy controls were evaluated using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
14
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 45 publications
4
14
0
3
Order By: Relevance
“…Consistent with hypothesis H2, the present findings indicate that women with acne have higher Type D personality scores than their counterparts without acne. This result is also consistent with a previous study regarding acne [ 85 ] and the extensive scientific literature on the relationship between Type D personality and various somatic diseases and mental problems or disorders [ 62 ]. Moreover, the findings suggest that the relationship between Type D personality and health outcomes may be generalized across different chronic illnesses [ 70 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Consistent with hypothesis H2, the present findings indicate that women with acne have higher Type D personality scores than their counterparts without acne. This result is also consistent with a previous study regarding acne [ 85 ] and the extensive scientific literature on the relationship between Type D personality and various somatic diseases and mental problems or disorders [ 62 ]. Moreover, the findings suggest that the relationship between Type D personality and health outcomes may be generalized across different chronic illnesses [ 70 ].…”
Section: Discussionsupporting
confidence: 93%
“…Type D personality is also related to low levels of positive affect, poor quality of life and self-esteem, high mental distress, post-traumatic stress disorder, depression, and social and general anxiety [ 60 , 63 , 64 , 65 , 66 , 68 , 72 , 76 , 79 , 80 , 82 , 83 , 84 ]. Moreover, Type D personality is positively associated with acne vulgaris [ 85 ] and negatively with life satisfaction [ 71 , 82 , 86 , 87 , 88 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acne, which is one‐quarter of the applications among all diseases, was in this group. Various studies have shown that depression, anxiety disorders, and body dysmorphic disorder are higher in acne patients 24,25 . Also, it was reported that there was a significant effect on the QoL, depending on the severity of acne 26 .…”
Section: Commentmentioning
confidence: 99%
“…Various studies have shown that depression, anxiety disorders, and body dysmorphic disorder are higher in acne patients. 24,25 Also, it was reported that there was a significant effect on the QoL, depending on the severity of acne. 26 Some diseases (such as psoriasis, urticaria/angioedema and Behçet's disease) requiring follow-up can seriously impair patients' QoL when they are severe.…”
mentioning
confidence: 99%